The selfish giant [videorecording (DVD)] - Barnard, Clio; Chapman, Conner; Thomas, Shaun; Gilder, Sean, 1964-; Wilde, Oscar, 1854-1900
A contemporary take on the Oscar Wilde fable, thirteen year old Arbor and Swifty are best friends for whom the joys of boyhood are almost nonexistent. They seek their fortune by getting involved with a local scrap dealer and criminal, leading to tragic consequences.